2008
DOI: 10.1007/s10637-008-9153-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase Ι trial of weekly Docetaxel and daily Temozolomide in patients with metastatic disease

Abstract: The combination of docetaxel and temozolomide was well tolerated and these agents can be safely combined. For phase II trials, docetaxel 35 mg/ m(2) IV day 1, 8 and 15, and daily temozolomide at 100 mg/ m(2) day 1-21 are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…This TMZ suspension could be easily administered via a nebuliser in NSCLC patients and in patients with pulmonary metastases. TMZ is currently undergoing a large number of clinical trials (Lefranc et al, 2007), including trials with NSCLC patients (Choong et al, 2006;Tamaskar et al, 2008;Kouroussis et al, 2009), and its therapeutic benefits have been demonstrated in cancers associated with extremely poor prognoses, such as glioblastomas (Lefranc et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This TMZ suspension could be easily administered via a nebuliser in NSCLC patients and in patients with pulmonary metastases. TMZ is currently undergoing a large number of clinical trials (Lefranc et al, 2007), including trials with NSCLC patients (Choong et al, 2006;Tamaskar et al, 2008;Kouroussis et al, 2009), and its therapeutic benefits have been demonstrated in cancers associated with extremely poor prognoses, such as glioblastomas (Lefranc et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…TMZ is active against cancers associated with extremely poor prognoses, such as glioblastomas and melanomas (Lefranc et al, 2007). TMZ has recently been assayed in various clinical trials relating to lung cancer patients (Choong et al, 2006;Tamaskar et al, 2008;Kouroussis et al, 2009). Systemic longterm TMZ administration can lead to hematological toxicities in cancer patients (Dario and Tomei, 2006;Gerber et al, 2007), but the TMZ delivery system that we propose here could lower the TMZ-associated toxicity found with systemic TMZ delivery, while maintaining anticancer activity.…”
Section: Introductionmentioning
confidence: 98%
“…Temozolomide has demonstrated antitumour activity against a broad range of tumour types, including malignant glioma, melanoma, NSCLC and carcinoma of the ovary and colon. In particular in the case of NSCLC, recent studies demonstrated that the combination of docetatel and temozolomide was well tolerated [36] and that the continuous low daily dose of temozolomide was associated with minimal toxicity in patients with NSCLC who had previously failed at least one chemotherapy regimen [37]. Therefore, the combination of low daily doses of temozolomide-which could result in a significant depletion of MGMT and enhance clinical activity [7,[38][39][40], with other anticancer drugs was suggested as another salvage option for patients with advanced NSCLC [37].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Combinations of both types of chemotherapeutic drugs have been applied as standard treatment regimens for various tumor entities, however, frequently evoking myelosuppression as a doselimiting side effect. [10][11][12] Various attempts were shown for chemoprotection of HSCs by retroviral transfer of MDR1 or MGMT. Gammaretroviral transfer of MDR1 into murine HSCs resulted in efficient chemoprotection against paclitaxel 13 or taxol.…”
Section: Introductionmentioning
confidence: 99%